Pemberdayaan Kader dalam Upaya Meningkatkan Kesehatan Tulang di Desa Kebumen Baturraden Banyumas - Made Sumarwati (Universitas Lancang Kuning, 2022)
Many people often pay less attention to care for their bones until their bones give them some problems. Efforts should be made to remind and enable everyone to care for and optimize bone health. The assessment of health cadres in Kebumen Village Regency Banyumas found the need for additional knowledge related to bone health. The purpose of this community program is to increase cadre knowledge related to bone formation and the changes that occur from the gestational into old age; optimizing bone health, including diet-related to calcium and Vitamin D intake, lifestyle, and its application in daily practice. This program has been done through training and providing learning media such as books and posters. This program has significantly enhanced knowledge, as evidenced by increasing the average knowledge and daily application practices. With qualified cadres, it is expected that everyone will be able to take good care of their bones.